PENGEMBANGAN KOMPETENSI UMKM DALAM UPAYA MENINGKATKAN KINERJA UMKM DI UMKM KAMEN TENUN PRANA SUTRA - Ni Luh Putu Eka Yudi Prastiwi; Ni Made Widnyani; I Nyoman Ade Mawan Setiawan (JUIMA : JURNAL ILMU MANAJEMEN, 2024)
The development of the competitiveness of UMKM is currently heavily influenced by various factors such as technology, finance, and production processes, and the most important sources are employees with intellectual capital/assets, skills, creativity, and information. Companies or UMKM that have employee capital with large intellectual/assets will the faster the UMKM progress and develop. Competence is said to be one of the factors that affect the performance of UMKM. This is closely related to the performance of SMEs. In the business world, one of them is in the Kamen Prana Sutra Weaving Business in Kalianget Village. The purpose of this study was to determine the effect of managerial and decision-making skills and managerial time on the performance of SMEs. The number of workers in the UMKM is 50 people who will be used in the sample in this study. This research was conducted using a quantitative approach. The data collection method used in this research is the method of distributing questionnaires and data analysis techniques using the SmartPLS application. The results of this study state that the parameter coefficient value of the relationship between Managerial and Decision Making Skills on UMKM Performance is 0.000 and the t-statistic value is 4.473, Human and Managerial Time on UMKM Performance moderated by skill and knowledge is 0.018 and the t-statistic value of 2,375. It can be stated that all constructs have a positive and significant effect.